2009
DOI: 10.1111/j.1365-3091.2008.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical gradational variability of fines deposited in a gravel framework

Abstract: Vertical gradational structures develop as sand infiltrates into static gravel beds. Understanding the vertical distribution of interstitial sand deposits will improve predictions of ecological suitability and hyporheic hydrodynamics. A series of flume experiments was performed to investigate fine infiltration processes. Four sand distributions were introduced into flows over gravel beds. After each experiment, bed cores were extracted and analysed in vertical layers to examine the gradational trends with dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(132 citation statements)
references
References 61 publications
7
122
2
1
Order By: Relevance
“…This behavior is consistent with the findings reported by Gibson et al (2009), who stated that bridging should occur for D 15 =d 85 Ä 10.6 (for the present H-G/S bed, D 15 =d 85 was equal to 4.5). The sand was too coarse to recirculate mixed with the water.…”
Section: Bed Materialssupporting
confidence: 93%
See 2 more Smart Citations
“…This behavior is consistent with the findings reported by Gibson et al (2009), who stated that bridging should occur for D 15 =d 85 Ä 10.6 (for the present H-G/S bed, D 15 =d 85 was equal to 4.5). The sand was too coarse to recirculate mixed with the water.…”
Section: Bed Materialssupporting
confidence: 93%
“…According to Gibson et al (2009), USP is the expected infiltration mechanism for D 15 =d 85 15.4, meaning that fine sediments should fill the beds from the bottom upwards. For these beds, the D 15 =d 85 ratio, representing the capacity of the coarsest fine grains .d 85 / to get through the finest coarse grains .D 15 /, was larger than 150.…”
Section: Bed Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects the high clogging potential of 0.5-1 mm compared to 0.125-0.5 mm particles and the ability of larger particles to bridge the interstitial spaces between grains, blocking pathways within the subsurface and reducing sediment porosity/permeability (Boulton et al, 1998;Bo et al, 2007;Vadher et al, 2015). The high clogging potential of the 0.5-1 mm particles was clearly exhibited in this study as this size fraction completely clogged the surface of mesocosms (bridging the majority of surface interstitial pathways) forming a physical barrier (Gibson et al, 2009) through which G. pulex could not penetrate. The deposition of fine sediment particles (\ 2 mm) within riverbeds has Table 2 Fisher's least significant difference (LSD) post hoc pairwise comparison of Gammarus pulex burrowing at the end of experiments in treatments 1-7 (see Table 1 Table 1.…”
Section: Discussionmentioning
confidence: 61%
“…The rate of supply, the grain sizes, the size and shape of the pores and the local morphology of the channel are among the many physical factors controlling the infiltration of fine particles (that can be of small gravel sizes) into alluvial frameworks [ Frostick et al , 1984]. In a flume experiment, Gibson et al [2009] observed rapidly filling zones of the bed just prior to or following the arrival of a bed load front. This process, combined with the natural heterogeneity of a gravel bed and the hyporheic exchanges associated mainly with the presence of bed forms, is an interesting hypothesis to explain the local increase or decrease of the proportion of fine particles within the bed.…”
Section: Discussionmentioning
confidence: 99%